(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper discusses how Salman Rushdie’s novel ‘Midnight’s Children’ delineates the religious, cultural and gender issues through magic realism technique. The novel presents the life of Kashmiri Muslim family. The women characters are delineated as humble at the beginning of the novel but as the story progresses they grow stronger and stronger. The animosity between the Hindus and the Muslims and the exploitation of Ravana Gang to gain profit by exploiting the Muslim merchants, the religious fanaticism of Muslim people who nearly killed a Hindu just for daring to enter in to their street, the effect of conservative Muslim upbringing and its impact on women characters, the linguistic riots and cultural conflict that caused the fall of Saleem Sinai’s MCC network are discussed in this article.